2021
DOI: 10.1016/j.eclinm.2021.100876
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of herpes simplex virus type 2 in sub-Saharan Africa: Systematic review, meta-analyses, and meta-regressions

Abstract: Background: Herpes simplex virus type 2 (HSV-2) infection is a prevalent, sexually transmitted infection with a sizable disease burden that is highest in sub-Saharan Africa. This study aimed to characterize HSV-2 epidemiology in this region. Methods: Cochrane and PRISMA guidelines were followed to systematically review, synthesize, and report HSV-2 related findings up to August 23, 2020. Meta-analyses and meta-regressions were conducted. Findings: From 218 relevant publications, 451 overall outcome measures an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 67 publications
8
56
1
Order By: Relevance
“…Unlike as in Africa, 21 Asia, 20 LAC, 22 and the United States, 42s–45s there was no evidence for declining HSV-2 seroprevalence in these countries. It is not known whether this lack of decline compared with other world regions could be a consequence of recent migration into these countries from countries with higher seroprevalence than in these countries.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Unlike as in Africa, 21 Asia, 20 LAC, 22 and the United States, 42s–45s there was no evidence for declining HSV-2 seroprevalence in these countries. It is not known whether this lack of decline compared with other world regions could be a consequence of recent migration into these countries from countries with higher seroprevalence than in these countries.…”
Section: Discussionmentioning
confidence: 84%
“…48s–52s,58s Herpes simplex virus type 2 genital herpes seems to affect men more than women (Table 5), but this may reflect the ease of clinically diagnosing this condition in men compared with women and/or disproportional contribution of genital herpes among MSM. 59s Herpes simplex virus type 2 seems to play a minor role in GUD, at only 17% (Table 4), lower than that found in Africa at 51%, 21 Asia at 48%, 20 and LAC at 41% 22 . However, only 5 GUD studies were identified in these countries; thus, they may not be representative of the true contribution of HSV-2 to GUD in these countries.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations